Legal Transformation in Limiting Human Rights in the Dilemma of Preventing Nepotism and Corruption - Andik Puja Laksana; Faisal Santiago (Cerdika: Jurnal Ilmiah Indonesia, 2024)
Legal transformation in restricting human rights (HR) has become a crucial issue in efforts to prevent nepotism and corruption. This phenomenon creates a dilemma between maintaining government integrity and protecting human resources, such as the right to freedom of politics, expression, and work. This study aims to explore how the law in Indonesia has changed in restricting human resources to prevent nepotism and corrupt practices and analyze whether these restrictions are in line with the principles of justice and proportionality. The research method used is normative law, with a legislative approach and case studies. Secondary data were collected through analysis of laws, regulations, and court documents related to corruption and nepotism. The research findings show that legal transformation in Indonesia has resulted in stricter regulations on conflicts of interest; however, in some cases, restrictions on HR are considered excessive, leading to potential violations of individual rights. In conclusion, although there is a need to control nepotism and corruption, it is important for the government to ensure that HR restrictions remain proportional and in line with international standards. The implication of this study is the need for more comprehensive, transparent, and accountable legal reform. The government needs to ensure that any anti-corruption regulations that restrict human rights are based on clear needs and are closely monitored to prevent abuse of power. Public involvement in oversight should also be increased to strengthen legal legitimacy and public trust.